2013
DOI: 10.5380/ce.v18i4.34917
|View full text |Cite
|
Sign up to set email alerts
|

Doenças Sexualmente Transmissíveis: A Percepção Dos Adolescentes De Uma Escola Pública

Abstract: Este estudo descritivo de abordagem qualitativa buscou conhecer a percepção de adolescentes sobre doenças sexualmente transmissíveis. Foram entrevistados 30 adolescentes de uma escola pública de Diamantina -Minas Gerais, entre agosto e dezembro de 2012. As entrevistas transcritas sofreram o processo de identificação dos núcleos de sentidos e categorização pela Análise de Conteúdo e originaramse duas categorias: Conhecimento sobre doenças sexualmente transmissíveis e Formas de aquisição de informações sobre doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Adolescence is pointed out by interpersonal conflicts, physical, psychological and social transformations, and this phase is marked by the passage of puberty, which brings physiological and morphological changes, begins approximately at the age of 12 and permeates until the age of 18, according to the ECA (Statute of the child and adolescent). Adolescence is situated between childhood and adulthood, and it is during this period that the discovery of their sexuality, the individual as if, self-image, sexual option and attraction to the opposite sex or the same sex, being important in this phase the guidelines to prevent recurrent diseases of an unsafe sexual act (JARDIM et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Adolescence is pointed out by interpersonal conflicts, physical, psychological and social transformations, and this phase is marked by the passage of puberty, which brings physiological and morphological changes, begins approximately at the age of 12 and permeates until the age of 18, according to the ECA (Statute of the child and adolescent). Adolescence is situated between childhood and adulthood, and it is during this period that the discovery of their sexuality, the individual as if, self-image, sexual option and attraction to the opposite sex or the same sex, being important in this phase the guidelines to prevent recurrent diseases of an unsafe sexual act (JARDIM et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis with 126 students aged between 10 and 15 years old, a 79.4% prevalence of low back pain was found in girls and 57.1% in boys. According to that author, this occurs because during the puberty (a period corresponding to both infancy and adulthood, usually stretching from 12 to 18 years of age [30]) women develop earlier than men [16]. Consequently, the adaptation to tiring physical activities is lower, there is increase in the frailty of articulations, higher sensitiveness in several painful conditions, and the pain perception can be influenced by hormonal factors resulting from the puberty 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study (17) showed that the knowledge of STIs is not an unknown theme to adolescents. Most of them associate the proper prevention method with the use of condoms, and the use of contraceptives is not directly related to knowledge, as its effective use involves historical and cultural aspects, which can create obstacles to changes in behavior to ensure a safe sexual experience.…”
Section: Discussionmentioning
confidence: 99%